Pekan Penerimaan Anggota Baru GMNI Dalam Membentuk Anggota Marhaenis Yang Progresif Menuju Indonesia Emas 2045 - Ade Putra Ode Amane; Sri Ayu Laali; Freshdy Nia; Maria Ulfa; Rifat Hakim; Anggi Afriawan; Rika Afriliani Alapia (Jurnal Pengabdian Masyarakat Nusantara, 2022)
The research method in data collection uses primary data and secondary data and the technical model of data analysis uses an inductive model. The Week of Admission of New Members (PPAB) for the GMNI Luwuk-Banggai Branch Leadership Council will be held on 24-26 September 2022 at the General Assembly Hall (BPU) of Luwuk Village, Luwuk District, Banggai Regency with the theme "Forming Progressive Marhaenis Members Towards a Golden Indonesia 2045". The participants of the activity were students from Luwuk Muhammadiyah University, Luwuk Tompotika University and Luwuk Banggai Computer and Informatics Management Academy. There were 13 participants who passed the PPAB, namely Aprianto Dukalang, Gita Hi Musa, Moh. Nabil Saputra Samali, Aurel Juliana Sambuhak, Afriani Hamzah, Ronal Nang, Awaludin Mulayo, Wandrik Ndilaman, Rizki amaliyah, Yosua Arifin Wakim Avenda Gultom, Matias A. Pompana, Arbia Bidilah and Sarbia Sapae.